Vienna prelude - Thoene, Bodie (Minneapolis, Minnesota : Bethany House Publishers, 1989)
Elisa Lindheim, of Jewish heritage, and John Murphy, New York Times reporter, become entangled in a web of intrigue, danger, and conspiracy.
Keywords: Antisemitism -- Fiction; Religious fiction